Bimodal exciton-plasmon light sources controlled by local charge carrier injection - Merino, Pablo (Sci Adv, 2018)
Electrical charges can generate photon emission in nanoscale quantum systems by two independent mechanisms. First, radiative recombination of pairs of oppositely charged carriers generates sharp excitonic lines. Second, coupling between currents and collective charge oscillations results in broad plasmonic bands. Both luminescence modes can be simultaneously generated upon charge carrier injection into thin C(60) crystallites placed in the plasmonic nanocavity of a scanning tunneling microscope (STM). Using the sharp tip of the STM as a subnanometer-precise local electrode, we show that the two types of electroluminescence are induced by two separate charge transport channels. Holes injected into the valence band promote exciton generation, whereas electrons extracted from the conduction band cause plasmonic luminescence. The different dynamics of the two mechanisms permit controlling their relative contribution in the combined bimodal emission. Exciton recombination prevails for low charge injection rates, whereas plasmon decay outshines for high tunneling currents. The continuous transition between both regimes is described by a rate model characterizing emission dynamics on the nanoscale. Our work provides the basis for developing blended exciton-plasmon light sources with advanced functionalities.